Political Participation of the Young Generation in the 2024 Regional Head Elections in Lubuklinggau City - Deny Nofriansyah; Januar Eko Aryansah (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2025)
This study examines youth political participation and electoral expectations in the 2024 Local Election of Lubuklinggau City, with a particular focus on university students as strategic voters in local democracy. Despite their growing demographic dominance, youth participation is often characterized by high electoral turnout but limited deliberative engagement. This research aims to analyze voting intention, attitudes toward money politics, sources of political information, priority issues, and factors influencing candidate preferences among young voters. The study employs a quantitative approach using a survey method involving 442 student respondents aged 18–35 years. Data were collected through structured questionnaires and analyzed using descriptive statistics and simple inferential techniques. The findings indicate that youth voting intention is relatively high; however, political participation remains largely procedural rather than discursive. Most respondents demonstrate a strong normative rejection of money politics and rely heavily on social media as their primary source of political information. Education costs, employment opportunities, and living expenses emerge as the most influential policy issues shaping electoral preferences. This study contributes to the literature on local democratic participation by highlighting the gap between electoral participation and substantive political engagement among young voters. The findings underscore the importance of strengthening political education, media literacy, and program-based digital campaign strategies to enhance the quality of youth participation in local elections.